Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pntd.0004865
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Hospital Management of Amphotericin B Deoxycholate-Related Toxicities during Treatment of HIV-Associated Cryptococcal Meningitis in South Africa

Abstract: BackgroundWe aimed to establish the prevalence of amphotericin B deoxycholate (AmBd)-related toxicities among South African patients with cryptococcosis and determine adherence to international recommendations to prevent, monitor and manage AmBd-related toxicities.MethodsClinical data were collected from cases of laboratory-confirmed cryptococcosis at 25 hospitals, October 2012 –February 2013. Anemia was defined as hemoglobin (Hb) concentration <10 g/dl, hypokalemia as serum potassium (K) <3.4 mEq/L and nephro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…More importantly, the FFP choice of food vehicles (i.e., staple foods such as maize meal and flour) is possibly reaching many South Africans, even in the remote rural areas. Prior studies have associated the Hb levels of Africans with a multitude of factors, such as food and nutrition insecurity, suboptimal diets as a result of poverty due to socioeconomic deprivation, and infection due to chronic and/or infectious diseases . It was therefore important to investigate the changes in the prevalence of anemia, ID, and IDA over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the FFP choice of food vehicles (i.e., staple foods such as maize meal and flour) is possibly reaching many South Africans, even in the remote rural areas. Prior studies have associated the Hb levels of Africans with a multitude of factors, such as food and nutrition insecurity, suboptimal diets as a result of poverty due to socioeconomic deprivation, and infection due to chronic and/or infectious diseases . It was therefore important to investigate the changes in the prevalence of anemia, ID, and IDA over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Iron stores/red blood cells can also be diminished during menstruation, during bouts of infections, and as a result of chronic non‐communicable diseases (NCDs) . Hence, the research done in Africa has shown that this condition is more prevalent/common among women of reproductive age, people who have limited access to basic needs (such as sanitation and treated water), and people exposed to infectious diseases and those at risk of NCDs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, SYBR Green and TaqMan were 100% specific. High specificity is the most important characteristic of any ATL diagnostic test, as the unjustified prescription of pentavalent antimonials or amphotericin B for patients without ATL can be extremely harmful (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In 10% (4/41) of included studies, the period of observation began prior to 2000. Seventeen countries were represented, with greatest representation from South Africa (14 studies) [34,[37][38][39][40][41][42][43][44][45][46][47][48][49], Ethiopia (three studies) [50][51][52] and Uganda (three studies) [53][54][55]; other countries had two or fewer studies [11,35,36,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Amphotericin B-based induction therapy (with or without fluconazole) was the predominant induction regimen in 16 studies, fluconazole in 13 studies, and a mix of treatments (45% fluconazole and 43% amphotericin B) in one study [44], with antifungal regimens not specified in 11 studies.…”
Section: Overall Search Findingsmentioning
confidence: 99%